2018
DOI: 10.1089/lrb.2016.0045
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Lymphedema-Related Risk Factors in Early-Stage Breast Cancer

Abstract: Preoperative bioimpedance analysis demonstrated that ∼1/5 of the patients had subclinical lymphedema. Preoperative subclinical lymphedema is associated with obesity and the number of positive lymph nodes, and thus, treatment of the axilla in patients who are preoperatively detected to have subclinical lymphedema should be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
2
24
0
4
Order By: Relevance
“…In a recent study, lymphedema rates were also found to be higher in patients undergoing axillary lymph node dissection, and among those with a more advanced stage of disease, in addition to having a higher BMI [ 12 , 14 , 32 ]. Additionally, not only are obese women at greater risk for developing post-operative lymphedema, but obese women are also at a higher risk of pre-operative lymphedema [ 44 •, 45 ].…”
Section: Lymphedemamentioning
confidence: 99%
“…In a recent study, lymphedema rates were also found to be higher in patients undergoing axillary lymph node dissection, and among those with a more advanced stage of disease, in addition to having a higher BMI [ 12 , 14 , 32 ]. Additionally, not only are obese women at greater risk for developing post-operative lymphedema, but obese women are also at a higher risk of pre-operative lymphedema [ 44 •, 45 ].…”
Section: Lymphedemamentioning
confidence: 99%
“…Currently, there is no reliable way of distinguishing patients who are likely to develop lymphedema, but a consensus has been reached on some well-defined risk factors, including axillary lymph node dissection (ALND), which is associated with early-onset disease (22), regional lymph node radiotherapy, which is related to late-onset disease (22), high body mass index (BMI) at the time of breast cancer diagnosis (BMI ≥25 kg/m 2 ) (23), a high number of positive lymph nodes (>8) (24) and capsular invasion of the tumor (24).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Não existem muitos estudos mostrando a incidência de linfedema após quimioterapia neoadjuvante ou antes da cirurgia; uma das causas poderia ser o edema subclínico do membro superior que muitas vezes é subestimado. Estudo com mulheres indicadas à cirurgia para o câncer de mama constatou, por meio da bioimpedância, linfedema em 17,7% daquelas que não tinham sintomas clínicos, nem alteração da circunferência dos membros superiores 13 .…”
Section: Discussionunclassified
“…Em nosso estudo, a paciente desenvolveu linfedema após a quimioterapia neoadjuvante e o laudo histopatológico confirmou quatro linfonodos comprometidos. Iyigun et al 13 afirmaram que o comprometimento de linfonodos axilares é um fator de risco para o linfedema subclínico.…”
Section: Discussionunclassified